資料倉儲於圖書館管理應用之研究─以分析館藏圖書探討圖書採購決策 The Study of Applying Data Warehouse to Library Management-Acquisition Policy Marking Based on Collections Analysis - Jiann-Cherng Shieh; Yi-Chen Wei (Jiàoyù zīliào yǔ túshūguǎn xué, 2003)
近年來由於資訊爆炸與技術迅速發展，圖書館在實務運作上面臨人力資源、參考諮詢。館藏發展的種種困境。由於讀者與圖書館間密切關係的發生，多源自於流通行為，因此圖書館館藏的良窳與否，不但影響圖書館服務品質，更影響讀者對圖書館評價。而圖書採購仍是目前圖書館館藏之主要管道，因此如何訂定採購政策以確保並提昇圖書館的服務品質，被視為圖書館管理上一重要議題，於本文中我們利用資料倉儲技術，彙整圖書館自動化系統之資料庫、圖書館館際合作資料、學校系所教師專長與學生資料、選課資料等資料資源，以多維角度分析探究館藏現況與需求，以期能支援圖書館圖書採購之決策參考，進而增進圖書館服務的讀者滿意度。 Recent years, according to the challenges of inflating information rapidly and emerging technologies, libraries suffer from the issues of library collections, human resources management and the capability of consultations. The collection-related research topics are the most investigated ones. Mainly it is library circulation to cause the intimate relationships between readers and the libraries, so the quality of library collections can directly affect library services and readers evaluations. Meanwhile, book acquisitions are the major channels of collections in today s libraries. Then how to make acquisition policies to promote the quality of library services has become a critical subject in library management researches. In this paper, we apply data warehouse technology to integrate corresponding data sources about library databases, inter-library loans,courses and departments to analyze the collection situations in various views. The results are expected to support decision making in book selection thus to improve readers satisfaction in library services.